Pemanfaatan Instagram sebagai Media Promosi untuk Pemasaran Produk Hijab - Ayu Lestari, Mita; Andrie Wijaya, Shendy; Redjeki, Sri (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
This study examines a micro hijab business that was pioneered since college using a reseller business model with low risk and high profit potential. This business, which was initially a side business, has succeeded in growing thanks to an adaptive marketing strategy that utilizes technology and social media algorithms, especially Instagram. The main focus on the quality of visual content, market segmentation, and active interaction with customers increases engagement and organic reach. Educational and inspirational content also strengthens relationships with consumers. Data-based evaluation and insight features support responsive strategy adaptation to market changes. This study is limited to the Instagram platform and lacks quantitative financial and operational data. It is recommended that further research conduct comparative studies on various digital platforms and explore the latest marketing technologies such as artificial intelligence. The novelty of this study lies in the integration of entrepreneurship in academic activities and adaptive and sustainable data-based digital marketing innovations, becoming an example for other micro businesses and the development of digital entrepreneurship.